BIOFERTILIZANTE DE BOVINOS LEITEIROS APLICADOS EM UROCHLOA BRIZANTHA CV. MARANDU - GONÇALVES, Enrique Gabriel Gimenes; NASCIMENTO, José Maria do; VASO, Larissa Maria; VASCONCELOS, Bruno Vieira (ANAIS DO ENIC, 2017)
-